2021
DOI: 10.1590/s1983-41952021000200014
|View full text |Cite
|
Sign up to set email alerts
|

Partial replacement of Portland cement with industrial glass waste in mortars

Abstract: The necessity to reduce the consumption of cement in cementitious composites is a worldwide concern and the partial replacement of cement with industrial waste has gathered considerable interest. One type of industrial waste is glass, which is rich in amorphous silica but can present problems with its use due to the alkali-silica reaction (ASR). The objective of this study was to analyze the compressive strengths of mortars using ground glass residue (GLR). Milling times of 16 h and 32 h were conducted and GLR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…However, a much bigger share (about 70 %) is disposed in landfills [14][15]. A scientific literature review has shown that glass powder acts as a pozzolanic material in concrete, i.e., by reacting with portlandite it forms an additional C-S-H phase [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, a much bigger share (about 70 %) is disposed in landfills [14][15]. A scientific literature review has shown that glass powder acts as a pozzolanic material in concrete, i.e., by reacting with portlandite it forms an additional C-S-H phase [16].…”
Section: Introductionmentioning
confidence: 99%